Pengembangan Instrumen Penilaian Kemampuan Pemecahan Masalah dalam Konsep Perhitungan Kimia - Sri Rubiati; Isana Supiah Yosephine Louise (Postgraduate, University of Mataram, 2025)
Measuring students' abilities through assessment instruments correctly is very useful so that teachers can guide students effectively. The development of assessment instruments often does not follow formal and scientific preparation steps, so that valid instruments are needed and measurements of problem-solving abilities can produce accurate and correct measurements. Problem solving is a complex activity involving broad objectives in the form of understanding problems, developing strategies, implementing strategies and interpreting results. This study aims to develop an assessment instrument for problem solving skills and to determine the characteristics of the problems solving skills assessment instrument in the concept of chemical calculations. This study uses a 4D development model consisting of the define, design, develop and disseminate stages. The test subjects in this study were 210 high school students. The results of the study showed that: The assessment instrument developed was in the form of 13 descriptive questions arranged based on indicators of problems solving skills; The assessment instrument fits the Rasch PCM 1-PL model in the range of 0.84 logit - 1.16 logit (valid), the reliability estimate is 0.62 reliable category and the level of difficulty of the questions - 0.38 logit to 1.00 logit (good category).